PENGARUH PENGGUNAAN LKS BERORIENTASI PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW BERMUATAN NILAI KARAKTER TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 1 RAO PASAMAN - Iwan Saputra; Yulkifli Yulkifli; Fatni Mufit (PILLAR OF PHYSICS EDUCATION, 2015)
This research is grounded by poor student’s learning outcomes in physic subject; many students have not reach KKM outcome in physic subject at school. The reason is students are not involved actively in learning process, and they are bored with current learning method. Interactions in learning are only one way. Poor student’s character in learning is because there is no subject that will guide transformation of student’s character. To deal with this problem, one of the efforts is using cooperative learning type jigsaw task book (LKS) with character value. The purpose of this research is to find out the effect of cooperative learning type jigsaw LKS with character value for student’s learning outcome of physic subject in X class SMAN 1 Rao Pasaman. The type research is “quasi experimental research” with “randomized posttest only control group” which population is students in nine classes of X class SMAN1 Rao Pasaman year of school 2013/2014. Sample was collected by cluster random sampling. Research data covered three domains that are cognitive, affective, and psychomotor. Research instruments are student’s grade, observation sheet of student’s affection and psychomotor. Data were analyzed by t-test. Based on data analysis, it showed that average cognitive domain in experimental classes was 82 and in control class were 77; average affection domain in experimental classes was 83.2 and in control class was 78.5; average psychomotor domain in experimental classes was 83 and in control class was 78.9. T-test in cognitive domain was thit = 3.57 and ttab = 2.00; T-test in affective domain was thit = 2.47 and ttab = 2.00; T-test in psychomotor domain was thit = 3.21 and ttab = 2.00. It means that those three domains have thit > ttab, so hypothesis is accepted in rate of 0.05. Conclusion this research is there is a significant effect of cooperative learning type jigsaw LKS with character value for student’s learning outcome of physic subject in X class SMAN 1 Rao Pasaman